Abridged Symbolic Representation of Time Series for Clustering - Korzeniewski, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
In recent years a couple of methods aimed at time series symbolic representation have been introduced or developed. This activity is mainly justified by practical considerations such memory savings or fast data base searching. However, some results suggest that in the subject of time series clustering symbolic representation can even upgrade the results of clustering. The article contains a proposal of a new algorithm directed at the task of time series abridged symbolic representation with the emphasis on efficient time series clustering. The idea of the proposal is based on the PAA (piecewise aggregate approximation) technique followed by segmentwise correlation analysis. The primary goal of the article is to upgrade the quality of the PAA technique with respect to possible time series clustering (its speed and quality). We also tried to answer the following questions. Is the task of time series clustering in their original form reasonable? How much memory can we save using the new algorithm? The efficiency of the new algorithm was investigated on empirical time series data sets. The results prove that the new proposal is quite effective with a very limited amount of parametric user interference needed.